PENGARUH SOSIALISASI PERPAJAKAN, PELAYANAN FISKUS, DAN SANKSI TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI (Studi pada Wajib Pajak Orang Pribadi di KPP Pratama Ponororgo) - Yuliasari, Wirda Salisa (Jurnal Mahasiswa Perpajakan, 2015)
This research aims to explain and analyze the effect of Tax Socialization, Tax Authority Service  and The Sanction against Personal’s Tax Compliance. The type of the research used is quantitative and the method is explanatory research for this aims to identify the effect of certain variable against others on the strictly-controlled condition. There are all taxpayers assessable populations of the research coped in the area of KPP Pratama Ponorogo and 90 respondents are taken out as a sample by using accidental sampling technique. Based on the result analyzed, there is an insignificant effect of the tax socialization  resulted against the personal’s tax compliance  with the 0,060 significance higher than the 0,05 significance. Additionally, there comes a significant effect of the tax authority service  against the personal’s tax compliance  with the 0,00 significance smaller than the 0,05 specified value. In the third variable, there is a significant effect of the sanction variable  against the personal’s tax compliance  with the 0,031 significance smaller than the 0,05 significance. The suggestion proposed on this research is that the revenue officer should improve the service in term of facility, equipment, and qualified human resources. Keywords: Sanction, Tax Authority Service, Tax Socialization, The Personal’s Tax Compliance.